Utilization of Smartphone in Building Cohesiveness Ecovillage Facilitator Group in Citarum Hulu River Area - NOVIANTI, Evi; BAKTI, Iriana; PERBAWASARI, Susie; ANWAR, Rully Khairul (Journal of Environmental Management and Tourism; Vol 9 No 7 (2018): JEMT Volume IX Issues 7(31) Winter 2018, 2019)
Ecovillage is one of the environmentally friendly village development programs in the Citarum Hulu watershed area of Bandung Regency which involves various parties as stakeholders. In implementing the program, stakeholders, who are the leading sectors, form networks that originate from communities living around the ecovillage development area to become facilitators. The system utilizes smartphone media so that mutual understanding and trust are built which underlies the cohesiveness of groups among these facilitators in the development of ecovillage in their target areas. This study aims to identify the motives for using smartphones in the development of ecovillage, and the factors that shape the cohesiveness of the facilitator group. The method used in this study is a descriptive method with qualitative data properties. The informants who were sampled in this study were facilitators who carried out assistance in three purposively selected target areas. The results showed that the motives of the facilitator used a smartphone with WhatsApp application to facilitate socialization and assistance in the development of the ecovillage which is easier to send messages, inexpensive concerning cost, simple, and fast. While the motive of using the Facebook application is easy to upload and share photos and various activities, affordable costs, easy to find friends, discussion sites, and places to study, the factors that shape the cohesiveness of the facilitator group are the development of cooperation, positive emotions, and the similarity of views in the development of the ecovillage.